Pengaruh Analisis Jabatan, Pengembangan Karir, Disiplin Kerja, Dan Prestasi Kerja Terhadap Kepuasan Kerja Pada Dinas Kesehatan Kabupaten Labuhanbatu - Jumianto, Jumianto; Pristiyono, Pristiyono (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of Job Analysis, career development, work discipline, and job performance on job satisfaction at the Labuhanbatu District Health Office. Based on the results of research conducted, there is a significant influence simultaneously (together) between the independent variables (Job Analysis, career development, work discipline, and job performance) affect the dependent variable (job satisfaction). This is evidenced by the obtained Fhitung value of 25.199 which is greater than the value of Ftable of 2.47. In addition, it is partially known that the position analysis (X1) has a positive and significant effect on job satisfaction (Y). This is evidenced by the obtained value of thitung greater than ttable (2.762>1.665) and the value of the coefficient of 0.292 and marked positive. Career development (X2) has a positive and significant effect on job satisfaction (Y). This is evidenced by the obtained value of thitung greater than ttable (2.159>1.665) and the value of the coefficient of 0.116 and a positive sign. Work discipline (X3) has a positive and significant effect on job satisfaction (Y), this is evidenced by the value of the calculation is greater than ttable (2.329>1.665) and the value of the coefficient of 0.232 and marked positive and job performance (X4) has a positive and significant effect on job satisfaction (Y). This is evidenced by the obtained value of thitung greater than ttable (2.964>1.665) and the value of the coefficient of 0.280 and a positive sign.Â